HERITAGE POLITICS AND MUSEUMS DURING JAPANESE OCCUPATION PERIOD, 1942-1945 - Arainikasih, Ajeng Ayu (International Review of Humanities Studies, 2021)
Before the World War II, approximately 25 museums were already established in colonial Indonesia. At that time, most of the museums were built by the Europeans to serve their interests. However, when the Dutch capitulated to the Japanese military government, what had happened to the existing museums in Indonesia were slightly known. Therefore, this research examines the history of the museum development during the Japanese occupation period in Indonesia in 1942-1945. The data gathered for this archival study are through magazine and newspaper articles published during the Japanese occupation period as well as through the archives of Arsip Nasional Indonesia, Jakarta. This research discovered that, during the Japanese occupation period, museums were used by the Japanese military government as their tool for political propaganda. This research also found out that during the Japanese occupation, politics and museums were closely entangled. Therefore, this preliminary research is important because it illustrates the history of museum development in Indonesia during the unknown period. It was also revealed that existing museums during that time had a significant impact for the museum development after Indonesian independence.